Rezension zu: Roebben, Bert: Theology made in Dignity - Krobath, Thomas (Österreichisches Religionspädagogisches Forum, 2020)
Rezension zu: Bert Roebben: Theology made in Dignity. On the Precarious Role of Theology in Religious Education, Leuven: Peeters 2016 (= Louvain Theological & Pastoral Monographs 44). ISBN 978-90-429-3416-0.